Migration as a form of workforce attrition: a nine-country study of pharmacists - Carter Sarah; Wuliji Tana; Bates Ian (BMC, 2009)
Abstract Background There is a lack of evidence to inform policy development on the reasons why health professionals migrate. Few studies have sought to empirically determine factors influencing the intention to migrate and none have explored the relationship between factors. This paper reports on the first international attempt to investigate the migration intentions of pharmacy students and identify migration factors and their relationships. Methods Responses were gathered from 791 final-year pharmacy students from nine countries: Australia, Bangladesh, Croatia, Egypt, Portugal, Nepal, Singapore, Slovenia and Zimbabwe. Data were analysed by means of Principal Components Analysis (PCA) and two-step cluster analysis to determine the relationships between factors influencing migration and the characteristics of subpopulations most likely and least likely to migrate. Results Results showed a significant difference in attitudes towards the professional and sociopolitical environment of the home country and perceptions of opportunities abroad between those who have no intention of migrating and those who intend to migrate on a long-term basis. Attitudes of students planning short-term migration were not significantly different from those of students who did not intend to migrate. These attitudes, together with gender, knowledge of other migrant pharmacists and past experiences abroad, are associated with an increased propensity for migration. Conclusion Given the influence of the country context and environment on migration intentions, research and policy should frame the issue of migration in the context of the wider human resource agenda, thus viewing migration as one form of attrition and a symptom of other root causes. Remuneration is not an independent stand-alone factor influencing migration intentions and cannot be decoupled from professional development factors. Comprehensive human resource policy development that takes into account the issues of both remuneration and professional development are necessary to encourage retention.